Glorious rubber stamping ideas, tips & techniques - Ritchie, Judy; Kilmartin, Jamie; Conron Carola, Leslie ([Place of publication not identified] Hugh Lauter Levin Associates, Inc., 2005)
Rubber stamping is an ideal way to add a personal touch to handmade cards and gift packages. A jar of fresh jam or herbed vinegar, some dried fruit and nuts, and a fragrant potpourri make wonderful homemade gifts. This collection of nearly 200 projects covers every aspect of creating rubber stamp projects. Inks, papers, borders, frames, boxes, folding (origami, iris folding, and tea-bag folding), tearing, punching, stitching, weaving, quilling, pop-outs, and other 3-D effects are all here with step-by-step instructions and colorful illustrations.
Simple rubber stamping -- Embossing -- Punching, folding & tearing -- Weaving, stitching & quilling -- Embellishing -- Above and beyond.
Includes bibliographical references.
Keywords: Rubber stamp art; Rubber stamp printing; Paper work